International handbook of threat assessment - Meloy, J. Reid; Hoffmann, Jens (Oxford University Press, 2021)
"This introductory chapter sets forth three foundations for threat assessment and management: the first foundation is the defining of basic concepts, such as threat assessment and threat management; the second foundation outlines the similarities and differences between threat assessment and violence risk assessment; the third foundation is a detailed overview of the research findings, theoretical avenues, measurement instruments, and developments in practice over the past quarter century. The goal of our chapter is to introduce the professional reader to the young scientific field of threat assessment and management, and to clarify and guide the seasoned professional toward greater excellence in his or her work"--